Cuts both ways: Ethnicity, poverty, and the social gradient in child welfare interventions. (October 2020) - Webb, Calum; Bywaters, Paul; Scourfield, Jonathan; Davidson, Gavin; Bunting, Lisa
Highlights: Significant ethnic inequalities in child protection, controlling for deprivation. The social gradient is strongest for White and Mixed Heritage populations. No evidence of a social gradient for Indian and Bangladeshi populations. Weaker social gradients for some interventions for other populations. Child welfare inequalities must be understood through an intersectional lens. Abstract: This article presents the findings of a quantitative intersectional analysis of child welfare interventions within small area ethnic populations in England. Recent research has highlighted that White British children, on average, have higher rates of intervention than children from other ethnic groups in poorer neighbourhoods and lower rates in more affluent neighbourhoods. This raises the question of whether structural associations between poverty and child welfare interventions apply equally to children from all backgrounds, or whether recent research into socioeconomic child welfare inequalities is largely capturing differences between ethnic groups. We investigate this question using multilevel negative binomial regression models predicting rates of children in need, children on child protection plans, and children in State care in ethnic group populations within geographical areas with average populations of 7200 children and adults. We find significant differences in ethnic group intervention rates, depending on levels of deprivation. Available data have significant limitations, but intersectional analysis identifies that a social gradient does not apply to, or is much smaller for, many ethnic populations and is strongest for White and Mixed Heritage populations. Socioeconomic inequalities in child protection are highly contingent on the ethnicity of the population, reflecting broader sociological literature related to race and class. This limits the generalisability of non-intersectional child welfare inequalities and introduces new avenues and imperatives for research seeking to better understand both ethnic and socioeconomic inequalities in children's social services. We consider that, beyond institutional racism, social work may need to grapple with complex forms of 'institutionalised intersectional injustice'.